Ethogram of Limulus polyphemus - Dylan K. Davidoff; Erin E. Frick (Animal Behavior and Cognition)
Developing an understanding of how organisms interact with their environment is crucial in creating best management practices in managed-care settings and improving conservation efforts. It similarly is important in understanding and developing research questions surrounding animal behavior and cognition. For many invertebrates, the knowledge surrounding behavior, welfare, cognition, and husbandry practices is greatly limited, posing a multitude of concerns when establishing these best management practices and general awareness for these animals. The American horseshoe crab (Limulus polyphemus; horseshoe crab), is often referred to as a living fossil species. However, their behaviors, like many invertebrates, are not well documented in scientific literature. This study presents the first peer-reviewed ethogram of Limulus polyphemus, operationally defining 47 behaviors. Horseshoe crabs were observed in both in-situ and ex-situ settings. The intention of this study was (1) to create a behavioral foundation that can be expanded upon and referenced, (2) to standardize the behavioral language regarding the species, (3) to demonstrate inter-rater reliability of the presented ethogram, (4) to propose potential applications, and (5) to further cultivate specialized research questions about horseshoe crab behavior.